Minocycline and Ifenprodil Prevent Development of Painful Diabetic Neuropathy in Streptozotocin-induced Diabetic Rat Model - Ismail, Che Aishah Nazariah; Suppian, Rapeah; Aziz, Che Badariah Abd; Long, Idris (IJLSCI, 2016)
mellitus which hugely affect life routines and quality. We aimed to investigate the effects of minocycline and ifenprodil on nociceptive behavior response, oxidant-antioxidant status and pro-inflammatory markers level in the PDN rat’s spinal cord. Forty-eight male Sprague-Dawley rats were divided into six groups (n=8): non-diabetic control, diabetic PDN control, diabetic PDN rats received minocycline (80μg/day or 160μg/day) and diabetic PDN rats received ifenprodil (0.5μg/day or 1.0μg/day). Diabetes was induced by single injection of streptozotocin at 60mg/kg. The rats were allowed for two weeks period to develop into PDN condition. The intrathecal treatments were given for seven days period. The rat’s hind paw was then injected with 5% formalin to induce chronic inflammatory pain and sacrificed three days post-formalin injection. Spinal cord tissue was removed and homogenized (10% homogenate). ELISA for oxidant-antioxidant markers (MDA, catalase and SOD) and pro-inflammatory markers (TNF-α and IL-1β) were carried out. The results showed that untreated PDN rats exhibited increased nociceptive behavior responses indicating hyperalgesia apart from increased MDA activity, reduced catalase with insignificant change in SOD enzymes activities, increased TNF-α and insignificant change in IL-1β level. Minocycline and ifenprodil suppressed MDA activity and improved catalase and SOD activities. Minocycline attenuated both pro-inflammatory cytokines whilst ifenprodilreduced TNF-α level but increased IL-1β level. In conclusion, minocycline and ifenprodil showed potent anti-nociceptive, anti-oxidant and anti-inflammatory effects but possibly via different pathway and mechanism.